Sport for Development and Peace: Power, Politics, and Patronage. Issue 3 (1st October 2016) - Giulianotti, Richard; Hognestad, Hans; Spaaij, Ramón
ABSTRACT: Sport for development and peace (SDP) is a rapidly growing field of activity in which sport is used as an intervention tool in order to pursue wider, non-sporting social goals. Organized into three main parts, this paper examines issues of power, politics, and patronage with respect to the SDP sector's organization and the implementation of programs particularly in the global South. First, drawing on a sociological approach broadly derived from Pierre Bourdieu, we examine how the SDP sector is structured, featuring a variety of stakeholders with different interests and aspirations; we explore in particular the potential influence of relatively marginal campaign groups and new social movements. Second, we identify the complex issues and challenges of patronage and mutuality that arise in international SDP work involving the global North (donor) and global South (recipient) in the post-colonial context. Third, we consider how these issues impact upon the design, implementation, and effects of SDP programs with particular reference to relations of power between the global North and South. We conclude by advancing the case for a "bottom-up", and more culturally and politically sensitive approach to be adopted by SDP stakeholders, particularly those based in the global North.